ELEMEN JURNALISTIK JUGA UNTUK BLOGGER? - Harnita, Pratiwi Cristin (Interaksi: Jurnal Ilmu Komunikasi, 2015)
AbstractIn this modern era, many changes occurred in the realm of communication in terms of both theory until the medium is one that is popular is the emergence of blogs. Remarkable development occurred, how ordinary people who could be a writer. This phenomenon show that not only journalists, or the scholar, but the housewife can be a writer for the blog. Nowadays, blogs became powerfull with such a information. Why powerfull? It’s because of freedom of journalistic that democracy to flourish. Blogs makes citizen very interesting, especially issues that do not appear in conventional mass media can be found in the personal blog as official criticism or goverment. Blogger can write many issue without pressure from press management or goverment. That’s why blogging activity is a part or citizen journalism. Some bloggers assume that the blog is open daily record then he can freely express their aspirations with either negative or positive. But now, the role of blogs far beyond the thinking of professional journalists, it turns out the blog evolved not only as a diary of course, but turned into a source of information most sought-after today. Bloggers need to know the elements of journalism. So, citizen journalists should be based on the nine elements of journalism and the foremost is the motivation behind any posts made. Most off all, the value basic of elemen journalistism for citizen journalism is indepency, freedom and social responcibility. In the end, blogging is how citizen journalists in good faith sharing information with each other. Thus the writings of the bloggers will be more meaningful and quality.